STUDENTS OBSTACLES IN SPEAKING SKILLS AT THE ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF MUHAMMADIYAH UNIVERSITY - Shifa Alviony Umasangadji; Sutaryo Sutaryo; Roswita M. Aboe (Jurnal Bilingual, 2023)
The purpose of this study was to determine the students' obstacles in speaking skills. This research was conducted offline and distributed questionnaires to students. The subject in this study were fifteen students in fifth semester at the English Education Study Program of Muhammadiyah University. This study used a qualitative method and a questionnaire was used as an instrument to obtain the necessary data. The data analysis technique is descriptive analysis. From the results of the data, it shows that the fifth semester students experience problems in speaking English fluently they cannot acquire vocabulary properly, the lack vocabulary and are unable to use parts of speaking English fluently.